The person behind the contact lens. Issue 9 (September 2021) - Retallic, Neil
Abstract : In an article based heavily on his BCLA presidential address broadcast last week, newly appointed BCLA president Neil Retallic takes a holistic approach to eye care and considers how this can influence the successful wear of contact lenses.